South-South cooperation as a driver of foreign action: the cuban experience - Juan Diego Ruiz Cumplido (Revista Española de Ciencia Política, 2015)
South-South cooperation (SSC) has over seventy years of experience, although a due attention has not always been focused on it. Although there is a dense rhetoric trying to keep SSC away of the traditional North-South cooperation (NSC), emphasizing its more horizontal and its untied character, this paper tries to argue the role that the SSC has as an instrument of foreign policy of countries. To support this point, a review is made of the broad SSC promoted by Cuba, a key driver in this context. Given the shortcomings in the systems of information of Cuban cooperation, one of the contributions of this paper is to provide systematic information on this subject, to support the suggested hypothesis.